Acute Pancreatitis in Patients With a Medical History of Type 2 Diabetes Mellitus: Clinical Findings and Magnetic Resonance Imaging Characteristics. Issue 4 (April 2020) - Xiao, Bo; Xu, Hai-bo; Jiang, Zhi-qiong; Hu, Jin-xiang; Yang, Guo-dong
Abstract : Objective: To determine the characteristics of type 2 diabetes mellitus (T2DM)–related acute pancreatitis (AP) on magnetic resonance imaging (MRI). Methods: Retrospectively studied 262 patients with AP were admitted to our institution and underwent MRI. Diagnosis of T2DM-related AP was based on clinical manifestations, laboratory tests, and MRI. Pancreatic/peripancreatic changes were assessed on MRI. Results: Fifty-three (20.2%) patients with T2DM-related AP and 209 (79.8%) with nondiabetic AP were enrolled. On MRI, a higher prevalence of necrotizing pancreatitis ( P < 0.001), pancreatic necrosis >30% (57.5% vs 29.2%; P = 0.006), hemorrhage (35.8% vs 19.1%; P = 0.009), abdominal wall edema (67.9% vs 46.8%; P = 0.006), walled-off necrosis (43.2% vs 14.6%; P < 0.001), and infected collections ( P < 0.001) were registered in T2DM with AP. T2DM-related AP sustained greater magnetic resonance severity index (mean, 5.1 [range, 2–10] vs 3.4 [range, 1–10]; P < 0.001), higher incidence of moderate and severe pancreatitis (69.8% vs 40.2%; P < 0.001), higher organ failure (45.3% vs 22%; P = 0.001), and prolonged hospitalization (mean, 25.2 [range, 10–63] vs 16 [range, 5–48] days; P < 0.001). Conclusions: Type 2 diabetes mellitus–related AP is more moderate-to-severe pancreatitis, and it correlates with MRI characteristics of the pancreas itself, hemorrhage, abdominal wall, and infected collections.